2018
DOI: 10.1177/0956462418774209
|View full text |Cite
|
Sign up to set email alerts
|

Genital mycoplasmas and ureaplasmas in cervicovaginal self-collected samples of reproductive-age women: prevalence and risk factors

Abstract: The purpose of this study was to characterise the prevalence and risk factors associated with genital mycoplasmas ( Mycoplasma hominis [MH], M. genitalium [MG]) and ureaplasmas ( Ureaplasma urealyticum [UU], U. parvum [UP]) in Portuguese women of reproductive age. The cross-sectional study included 612 cervicovaginal self-collected samples from women aged 15-44 years, tested for MH, MG, UU, UP by polymerase chain reaction. Y chromosome (Yc) DNA was detected as a biomarker of recent unprotected sexual intercour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
2
7
0
2
Order By: Relevance
“…38 Furthermore, there was no association between infection and age (P = 0.20), as some studies identified a higher risk of infection among women aged under 25 years. 34,36,38,39 We verified an association between the presence of infection and microbial dysbiosis, with a more extensive association between BV and Mh (54.3%) than between BV and Ureaplasma spp. (25.7%), in agreement with other studies.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…38 Furthermore, there was no association between infection and age (P = 0.20), as some studies identified a higher risk of infection among women aged under 25 years. 34,36,38,39 We verified an association between the presence of infection and microbial dysbiosis, with a more extensive association between BV and Mh (54.3%) than between BV and Ureaplasma spp. (25.7%), in agreement with other studies.…”
Section: Discussionsupporting
confidence: 58%
“…34,35 The association of genital mycoplasma infection with variables such as socio-economic status and behavioural habits, such as as sexual partners and the use of cigarettes, were also considered risk factors in other studies. 34,[36][37][38][39] On the other hand, the ethnicity of the pregnant women was not associated with infection (P = 0.15). 38 Furthermore, there was no association between infection and age (P = 0.20), as some studies identified a higher risk of infection among women aged under 25 years.…”
Section: Discussionmentioning
confidence: 96%
“…The use of intrauterine devices also could lead to higher STIs infection rate [38] . The women using unhygienic method during menstruation were more likely to have STIs symptoms and vaginal discharge [39] . Verteramo et al [6] found that in multi-logistic regression analysis, age (<35 years), intrauterine devices and sexual partners number were significantly associated with UU among 3115 women.…”
Section: Discussionmentioning
confidence: 96%
“…Verteramo et al [6] found that in multi-logistic regression analysis, age (<35 years), intrauterine devices and sexual partners number were significantly associated with UU among 3115 women. In Portuguese women of reproductive age (15-44 years), women aged 20-29 years was associated with an increased UU infection risk and lifetime numbers of sexual partners was one of predictors of UU infection [39] .…”
Section: Discussionmentioning
confidence: 99%
“…O Brasil, que representa 2,2% dos nascimentos mundiais, está na 9º posição dos países com maiores taxas de prematuridade (CHAWANPAIBOON et al, 2019). Estudos indicam que, além das complicações causadas ao neonato, os PPT também estão associados à altos custos aos serviços de saúde e dificuldades psicológicas e financeiras à mãe e familiares (KORVENRANTA et al, 2010;SINGER et al, 1999). Dessa forma, na perspectiva de melhorar o atendimento e a qualidade de vida materna e infantil, é necessário entender melhor a epidemiologia e fatores de risco relacionados ao PPT.…”
Section: 2unclassified